AUTHENTIC USE OF GRAMMAR - Tursunova Halima Boqijanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The main task of a foreign language teacher in the past was to teach grammatical structures without any context. Learners were not taught to communicate in the language. Such kind of approach to a language teaching caused teachers` difficulty in making the language classes interesting. Because of this, learners were not interested in learning a foreign language, namely, grammar. According to my observations, I can say, even some ESL teachers are confused why to teach grammar if learners don`t use it in real life .But today, when we say teaching grammar, we imply effective strategies, motivation, support and stimulation, refraining from obsolete methods and creating global programs. Authentic use of grammar is the very approach learners need. Grammar should be integrated into other language skills as listening, reading, speaking and writing. It encourages the active, purposeful and communicative use of grammar.